Making external political decision in traditional political systems - Ahmed Bassel Al - Bayati (الرافدین للحقوق, 2008)
The foreign policy industry includes several processes to define the rules of dealing with international variables and the development of a program of work in the international field. Foreign policy-making is one of the most important processes of the foreign policy industry. An external political decision is intended to take the final stage in the process of external political decision-making, namely the stage of choosing the best decision. This stage is one of the most dangerous stages because it can result in positive results for the benefit of the state or negative results that harm the interests of the state. Foreign policy decisions also constitute the overall course of the foreign policy of the international community.